ETHNOMATHEMATICS ON THE PATTERN AND PHILOSOPHY OF BATIK BANTEN MOTIFS - Sanifah, Sanifah; Amriyah, Siti; Jumaroh, Siti; Novianti, Nurul; Kusuma, Jaka Wijaya; Khan, Faisal (Yayasan Education and Social Center, 2022)
Mathematics is a science that studies logic, form, arrangement, magnitude, and interrelated concepts. One of the cultures owned by Banten is batik. This type of research method is a qualitative research method that uses ethnographic design. . This research instrument is the researcher himself. Based on the researchers' results and discussion, there are mathematical concepts in batik Banten motifs. Researchers can use mathematical concepts on Batik Banten motifs to wake up flat triangles, rectangles, circles, translation, and mirroring